Editorial (Indian Journal of Extension Education, 2022)
In January 2022, it was projected that the inflated prices for agricultural inputs and the demand for labour will be driving forces in 2022. Due to twin problems of low productivity and excess workforce employed in it, the per capita productivity of the workforce is very low which results in depressing the agriculture sector wages and ultimately the increased poverty. In our neighborhood, in Sri Lanka, fears of a hunger crisis are rising in, and rice production in the last harvest season had already plunged 40% to 50%. Due to the direst economic meltdown in Sri Lanka, seed and fertilizer scarcities could shrink crop yields by as much as 50%, whereas, on the other hand, Indian agricultural exports rose by about 20% to 50.21 billion during 2021-22 despite logistical challenges posed by the COVID-19 pandemic. The rise in export of agricultural and processed food products has been largely due to the various initiatives taken by the Centre Government through organizing B2B exhibitions in different countries, exploring new potential markets through product-specific and general marketing campaigns by the active involvement of Indian Embassies. The agricultural extension system needs to respond against a slowdown in growth; degradation of natural resource base; uneven and slow dissemination of technology; inefficient use of available technology and inputs and other abiotic stresses.